Good practices of basic education teachers during the COVID-19 pandemic (Revista Innova Educación, 2021)
The objective of this article was to analyze the actions that teachers from different states of the Mexican Republic implemented to give continuity to the learning activities of students during the health contingency. Grounded Theory was used as an analysis tool and interviews were conducted through video calls with an intentional sample of twenty teachers. The main findings indicate that: teachers reconceptualized their practice in a short time, adapting it to the context to face the crisis, used technological means to transmit topics and content, looked for alternatives to communicate with the students, generated didactic resources with instructional design, recorded videos and carried out activities to support the families socially emotionally, showed empathy and solidarity actions with the households. As a result of their professional experience, and knowledge, they managed to innovate in their discipline and respond to the demands of the environment, in contrast, the government strategy showed limitations.
Keywords: Distance education; elementary education; educational strategies; pandemics; practice teaching